Memory, History, and Displacement: Modern Subjectivity in Evelyn Waugh's Sword of Honor Trilogy - Horacki, Michael J. (Christianity & literature, 2025)
This article begins by analyzing Waugh’s treatment of the entry of “displaced persons” into the vernacular, arguing that WWII’s displacements and the struggles to survive that necessitated them are, for Waugh, the most grotesque consequences of modernity. After briefly tracing the relationship between displacement and modernity through his career, it argues Waugh’s final trilogy moves beyond his earlier critiques, presenting a character who draws on Church history, family collective memory, and the traditions of a family grounded in its historical faith to propose a mode of subjectivity that can withstand the dislocation Waugh sees as characterizing modernity.